Unveiling the difference in the activity and selectivity of nickel based cocatalysts for CO2 photoreduction. (February 2023) - Mo, Weihao; Chen, Qin; Zhou, Hao; Zhao, Wei; Hu, Lingxuan; Zhong, Shuxian; Ke, Sai; Wu, Xi-Lin; Chen, Jianrong; Bai, Song
Abstract: Seeking earth-abundant and high-performance cocatalysts is important and indispensable to achieve highly efficient artificial photoreduction of CO2 to solar fuels, an eco-friendly and sustainable approach to remedy environmental damage and address the energy crisis. Herein, as promising noble-metal-free candidates, six Ni species including Ni, NiO, NiS, Ni2 P, Ni3 C and Ni3 N were deposited on TiO2 nanosheets to evaluate their cocatalytic behaviors in photocatalytic CO2 reduction reactions. It is found that Ni and NiO cannot improve the photocatalytic activity dramatically, while NiS and Ni2 P substantially accelerate the side H2 evolution and drastically decrease the selectivity for CO2 reduction. Conversely, Ni3 C and Ni3 N significantly promote the CO2 -to-CO conversion and effectively inhibit the proton reduction reaction. In particular, the best-performing TiO2 -Ni3 N affords a maximum CO production rate of 49.6 μmol gcat −1 h −1 and supreme selectivity of 94.1 % for CO2 reduction. The origin of the activity and selectivity difference of Ni based cocatalyst is the distinct electron trapping abilities in separation of electron-hole pairs and varied surface reactivities in adsorption and activation of CO2 molecules. Theoretical simulations also reveal that the six Ni species possess diverse thermodynamic energy barriers for CO2 -to-CO conversion and side H2 generation. Results support the development of novel earth-abundant cocatalysts for solar energy conversion applications. Graphical Abstract: ga1 Highlights: Ni, NiO, NiS, Ni2 P, Ni3 C and Ni3 N nanocrystals were deposited on TiO2, respectively. Six cocatalysts exhibit different activities and selectivities in CO2 photoreduction. The origin is their distinct electron trapping and CO2 adsorption/activation abilities. Ni3 N delivers the highest CO evolution rate and supreme selectivity for CO2 reduction.